2017
DOI: 10.4103/ijc.ijc_56_17
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer: Presentation and pattern of care in a cancer center in South India

Abstract: Lung cancer is the major cancer affecting males in India with a high incidence in Trivandrum and a very low percentage of patients receiving curative treatment which could be due to the high prevalence of tuberculosis and scarce availability of facilities and trained manpower for thoracic oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Adenocarcinoma was also more common in the age group of 61-80 (55.81%) followed by 41-60 age group (33.72%) Table 6. DISCUSSION: In the present study, a male to female ratio of 4.8:1 was observed and another study from RCC Trivandrum, Kerala was also found the similar male to female ratio of 4.7:1 11 . The sex ratio reported in several Indian studies ranged from 4.5:1 to 8.2:1 21,22 .…”
Section: Exclusion Criteriasupporting
confidence: 85%
See 2 more Smart Citations
“…Adenocarcinoma was also more common in the age group of 61-80 (55.81%) followed by 41-60 age group (33.72%) Table 6. DISCUSSION: In the present study, a male to female ratio of 4.8:1 was observed and another study from RCC Trivandrum, Kerala was also found the similar male to female ratio of 4.7:1 11 . The sex ratio reported in several Indian studies ranged from 4.5:1 to 8.2:1 21,22 .…”
Section: Exclusion Criteriasupporting
confidence: 85%
“…There are studies which reported adenocarcinoma was the most frequent histological type of lung malignancy 25,37 . A study conducted at RCC Trivandrum, Kerala found that adenocarcinoma (28.5%) was the most common histology type followed by Squamous cell carcinoma (12.9%) 11 . However, the pattern seen at our study district was different and squamous cell carcinoma (48.74%) was still the most frequent, followed by adenocarcinoma (36.13%).…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…4 Despite considerable advancements in diagnosis and treatment, 5-year overall survival (OS) of LC patients remains below 15%. 5,6 Hence, prognostic markers and potential drug targets should be identified to enhance prognosis and individualized treatments.…”
Section: Introductionmentioning
confidence: 99%
“…El rendimiento de la biopsia endobronquial es mayor para lesiones exof铆ticas visibles por fibrobroncoscopia, con un rendimiento diagn贸stico aproximado del 90%. [23][24][25][26] Para los adenocarcinomas la tasa diagn贸stica es del 52.6% y para los carcinomas de c茅lula escamosa del 92%. 18 Dentro de los casos con fibrobroncoscopia negativa para lesi贸n tumoral y con histopatolog铆a positiva (n = 22) (tabla 2), llama la atenci贸n los 4 casos de linfoma (1 caso de linfoma Hodgkin cl谩sico tipo esclerosis nodular, 1 caso de linfoma B marginal, 1 caso de linfoma B difuso de alto grado y un caso de linfoma T extranodal NK), donde este hallazgo de ninguna lesi贸n endosc贸pica o no relacionada con neoplasia se debe a que la infiltraci贸n bronquial suele ser submucosa y no sobresale por la v铆a a茅rea.…”
Section: Resultsunclassified